All-trans retinoic acid prevents oxidative stress-mediated cellular senescence via upregulation of insulin-like growth factor binding protein-6 in normal human epidermal keratinocytes - Choi, Hyangtae; Lee, Jin Young; Park, Nok Hyun; Nam, Jin; Park, Won-seok; Lee, Chang Seok; Kim, Beom Joon (Archives of Biological Sciences, 2021)
Paper description: Potential mechanisms of action of all-trans retinoic acid (ATRA) in primary normal human epidermal keratinocytes (NHEKs) were examined. Microarray analysis using ATRA-treated NHEKs, insulin-like growth factor binding protein-6 (IGFBP-6) gene overexpression and knockdown systems, senescence-associated (SA)-β-galactosidase (Gal) staining, real-time PCR, Western blotting were performed. ATRA increased IGFBP-6 expression in NHEKs. IGFBP-6 / ATRA prevents H2O2-induced premature senescence (assessed by SA-β-Gal and p21) in ATRA ameliorates premature senescence in NHEKs at least partly via an IGFBP-6-dependent pathway. Abstract: All-trans retinoic acid (ATRA) influences cellular proliferation and differentiation but its mechanisms of action are not understood in keratinocytes. To investigate the potential mechanisms of action of ATRA in keratinocytes, microarray analysis of ATRA-treated normal human epidermal keratinocytes (NHEKs) was performed. Based on microarray data, we focused on insulin-like growth factor binding protein-6 (IGFBP-6), which is known to inhibit cellular senescence but has not been previously investigated in the context of ATRA-induced signaling in NHEKs. We verified that ATRA significantly increased IGFBP-6 gene and protein expression in NHEKs. Next, the effects of ATRA and IGFBP-6 on cell proliferation and senescence in H2O2-treated NHEKs were examined. IGFBP-6 was knocked-down using siRNA or overexpressed using pCMV-IGFBP-6. Cellular proliferation was observed using the bromodeoxyuridine (BrdU) incorporation assay. Cellular senescence was determined by monitoring SA-β-Gal staining and p21 expression. When IGFBP-6 was knocked down, cellular proliferation was inhibited, and the cellular senescence markers were increased. IGFBP-6 overexpression or ATRA treatment of H2O2-treated NHEKs rescued these effects. Taken together, our results suggest that ATRA prevents premature senescence-related skin damage at least in part by increasing IGFBP-6 expression, as shown herein in reactive oxygen species (ROS)-stimulated NHEKs.